QUANTITATIVE APPROACH TO ASSIST NEUROBLASTOMA ASSESSMENT BY MEASURING I-123 mIBG UPTAKE IN SCINTIGRAPHIC IMAGES - Martínez-Díaz, Rafael; Balaguer, Julia; Sánchez-Ruiz, Luis Manuel; Bello, Pilar; Castel, Victoria; Rivas, Antonio; Cañete, Adela; Falgas, Marina; Loaiza, Jose Luis; Perís-Fajarnés, Guillermo (Image Analysis and Stereology, 2015)
Whole-body 123I-Metaiodobenzylguanidine (mIBG) scintigraphy is used as the primary image modality in neuroblastoma detection. It is the most sensitive and specific method for staging and response evaluation. Validated semi-quantitative scoring methods with low interobserver variability and high reproducibility have shown to be indispensable for the evaluation of response to therapy. However, low resolution, noise and acquisition difficulties, specially in children, make low definition scans. These facts increase observer dependent interpretations that limit assessment and complicate to put a scoring method successfully into practice. It is essential to have an objective and reliable measure of response to test the activity of therapies. In this paper we propose the use of a quantitative observer-independent measurement of the strength of uptake to be used as an additional tool for assisting the International Society of Paediatric Oncology Europe Neuroblastoma Group (SIOPEN) semi-quantitative scoring method. This is the scoring method recommended by the SIOPEN Nuclear Medicine and Physics Committee, in collaborative work with the Children’s Oncology Group, as the standard one for acquiring and reporting diagnostic paediatric mIBG scans across Europe. Our proposed method is based on the ratio between the amount of specific uptake at tumours and the amount of non-specific uptake at SIOPEN anatomical sectors which has shown to be constant in all the scans of the patients.